PRAKTEK PELAYANAN KEFARMASIAN PADA RAWAT INAP-PT ASKES DI UNIT LOKET ASKES -IFRS -RS WANGAYA - I Made Agus Gelgel Wirasuta; Made Gede Praditya Putra; Ni Made Pitri Susanti (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2013)
Pharmaceutical care takes an essential role in order to realize the patient safety caring with effective medication cost. It was studied the pharmaceutical caring in pharmacy-clinic-Unit of Wangaye Hospital-Denpasar, which provided to the hospitalization patients of PT. Askes (Persero)-Cabang Denpasar and the role of  the health insurance verification.  Aim of the study was to observe the role of pharmacist and health insurance verification in order to realize the patient safety caring with effective medication cost. The pharmacist in this unit has strived for a pharmaceutical praxis according to the pharmaceutical regulation but not yet optimal utilized his praxis to obtain a rational use of drugs and effective medical cost. There was not a pharmacist, which was employed by PT ASKES to verify the pharmaceutical praxis, which provided pharmaceutical care to the ASKES patients.